Topical Atropine for Myopia Control: A Review - Farassat, Navid (Klinische Monatsblätter für Augenheilkunde, 2024)
Over the past decade, atropine has emerged as an effective intervention for preventing myopia in children. Multiple randomized controlled trials, mainly from Asia, have demonstrated the safety and efficacy of topical atropine for myopia control. Both efficacy and side effects exhibit a positive dose-response relationship. This review focuses on new data from studies with predominantly white populations, ethnicity-dependent differences in efficacy and side effects, and primary prevention of incident myopia with atropine.
Keywords: pediatric ophthalmology; myopia; myopia prevention; myopia control; myopia management; atropine